PEMAHAMAN HADIS TABARRUJ DAN KORELASINYA DENGAN NARSIS DI MEDIA SOSIAL TIK-TOK - Almunadi Almunadi; Eko Zulfikar (FiTUA: JURNAL STUDI ISLAM, 2023)
This article aims to examine the understanding of tabarruj hadiths and their correlation with the Tik-Tok social media. This is motivated by the tabarruj phenomenon which is heavily influenced by up-to-date trends and styles, which often appear on social media, especially Tik-Tok. By using qualitative methods and the science approach of ma’ani al-hadith, this study concludes that: First, the hadiths that talk about tabarruj have forbidden tabarruj actions with the threat of not going to heaven, such as dressing naked because the clothes are too minimal, thin, and see-through, clothes that are too tight which stimulate men because some of their private parts are open, walking with waddling, tattooing and changing limbs to beautify themselves, and so on. Second, what this hadith says resonates with Tik-Tok social media users, especially women who often use thick make-up, contact lenses, false eyelashes, display beauty to make them look attractive, show off jewelry that should be hidden, wear tight clothes with excessive swaying so that showing curves. This kind of tabarruj actually exceeds the tabarruj that occurred in the era of ignorance which only showed the jewelry and neck when veiled.